Structural modelling of Eu3+-based siloxane-poly( oxyethylene) nanohybrids - Dahmauche, K.; Carlos, L. D.; Bermudez, V. D.; Ferreira, RAS; Santilli, Celso Valentim [UNESP]; Craievich, A. F. (Royal Soc Chemistry, 2001)
The modelling of the local structure of sol-gel derived Eu3+-based organic/inorganic hybrids is reported, based on Small-Angle X-ray Scattering (SAXS), photoluminescence and mid-infrared spectroscopy. The hybrid matrix of these organically modified silicates, classed as di-ureasils and termed U(2000) and U(600), is formed by poly( oxyethylene) (POE) chains of variable length grafted to siloxane domains by means of urea cross-linkages. Europium triflate, Eu(CF3SO3)(3), was incorporated in the two di-ureasil matrices with compositions 400 greater than or equal ton greater than or equal to 10, n is the molar ratio of ether oxygens per Eu3+. The SAXS data for undoped hybrids (n=infinity) show the presence of a well-defined peak attributed to the existence of a liquid-like spatial correlation of siloxane rich domains embedded in the polymer matrix and located at the ends of the organic segments. The obtained siloxane particle gyration radius Rg(1) is around 5 Angstrom (error within 10%), whereas the interparticle distance d is 25 +/-2 Angstrom and 40 +/-2 Angstrom, for U(600) and U(2000), respectively. For the Eu3+-based nanocomposites the formation of a two-level hierarchical local structure is discerned. The primary level is constituted by strongly spatially correlated siloxane particles of gyration radius Rg(1) (4-6 and 3-8 Angstrom, errors within 5%, for U(600())n Eu(CF3SO3)(3), 200 greater than or equal ton greater than or equal to 40, and U(2000)(n)Eu(CF3SO3)(3), 400 greater than or equal ton greater than or equal to 40, respectively) forming large clusters of gyration radius Rg(2) (approximate to 75 +/- 10 Angstrom). The local coordination of Eu3+ in both di-ureasil series is described combining the SAXS, photoluminescence and mid-infrared results. In the di-ureasils containing long polymer chains, U(2000)(n)Eu(CF3SO3)(3), the cations interact exclusively with the carbonyl oxygens atoms of the urea bridges at the siloxane-POE interface. In the hybrids containing shorter chains, U(600)(n)Eu(CF3SO3)(3) with n ranging from 200 to 60, the Eu3+ ions interact solely with the ether-type oxygens of the polymer chains. Nevertheless, in this latter family of hybrids a distinct Eu3+ local site environment involving the urea cross-linkages is detected when the europium content is increased up to n=40.